2017
DOI: 10.15694/mep.2017.000201
|View full text |Cite
|
Sign up to set email alerts
|

Using the Dundee Polyprofessionalism Inventory I: Academic Integrity to Map Student Professionalism in 3 Arab Gulf Countries

Abstract: Background: Teaching professionalism and communication skills have become an integral part of medical education. But professionalism cultures may themselves be at least partially culturally determined. It would be helpful to be able to 'map' regional professionalism cultures especially in an era of increasing globalisation and international mobility of practising doctors within and across regional boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This study is among the few that have investigated professionalism among medical students in Saudi Arabia following the implementation of the SaudiMED framework to the new curriculum. 29 , 30 Secondly, this study used a questionnaire with high internal consistency and whose tenets have been validated in the Arabian context. 14 Finally, this instrument and/or the tenets of professionalism used by this instrument have been adapted to assess professionalism among medical students in other parts of the Arab region, Asia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is among the few that have investigated professionalism among medical students in Saudi Arabia following the implementation of the SaudiMED framework to the new curriculum. 29 , 30 Secondly, this study used a questionnaire with high internal consistency and whose tenets have been validated in the Arabian context. 14 Finally, this instrument and/or the tenets of professionalism used by this instrument have been adapted to assess professionalism among medical students in other parts of the Arab region, Asia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on academic integrity among Saudi students have shown that some students tended to recommend more lenient sanctions. 30 , 31 Thus, there is a need to strengthen the level of accountability during their training. Also, since professionalism is context-specific and culturally sensitive, there is a need to adapt the ‘Accountability’ subscale to fit the Arabic context.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the integrated and student-centered curricula stimulate and provoke students to be active learners; also, they develop and evolve their skills. 50…”
Section: Discussionmentioning
confidence: 99%
“…It has been translated into various languages, used in various countries for many years, and has been identified as a nonculturally specific questionnaire [ 21 , 22 ]. Some studies differed from consensus of cross-cultural adaptation process, such as multiple translators not participating, missing the back translation, or proceeding in a different order [ 26 , 48 51 ]. Some did not elaborate on whether they followed the consensus process or not [ 15 , 24 , 37 , 52 56 ].…”
Section: Discussionmentioning
confidence: 99%